Utilization of Waste Plastic Bags to Improve Stability of Para-Asphalt Concrete : A Case Study of the Entrance Road at Ao Nang Subdistrict Administration Organization, Krabi Province - Lakas, Wechsawan (Naresuan University Journal: Science and Technology (NUJST), 2019)
Utilization of waste plastic bags as an admixture to enhance the stability of para-asphalt concrete is a part of integrated solution to the problem of the continuous dropping of prices of natural rubber, a crisis for the rubber production industry, and the environmental crisis of accumulated plastic waste. The target community was Ban Thung Village, Moo 5, Tambon Ao Nang, Muang District, Krabi Province.  The process started from sorting out wastes to construct a prototype road for the community. It is found from this investigation that the community was able to segregate 200 kg of plastic bags, accounting to 1.83% of the total waste generated. These bags were then mixed into para-asphalt concrete in the laboratory and tested for its stability by the Marshall Test. It is revealed that the concrete samples with a 10% mixture of the waste plastic bags by weight of the para-asphalt concrete have the stability of 13.7 kN, which is higher than the 12.7 kN of regular para-asphalt concrete and 9.8 kN of the standard criterion specified by the Department of Highways. The concrete is able to be used for constructing a road or an activity field in the community by mixing 5 mm waste plastic bags into the asphalt concrete while surfacing the road. The temperature of the concrete should be higher than 140°C in order for the plastic to fully melt into the concrete. The road surface is then pressed solidly and open for public use. Keywords: Para-Asphalt Concrete,  Natural Rubber - Modified Asphalt Concrete,  Waste Plastic Bags